Disclosure of Adverse Events - An OSCE Series for OB/GYN Residents - Glenn Posner; Amy Nakajima (Association of American Medical Colleges, 2011)
Abstract Disclosing adverse events to patients after a poor outcome is an essential task involving both communication skills and professionalism. Assessing an individual resident's ability to perform a disclosure meeting during a clinical rotation is important, as it ensures clinical competency and is essential in minimizing medico-legal risk. However, disclosures may be difficult to teach and assess during clinical rotations. This opportunity may not arise during the rotation, and an attending physician may not be present during the occasion whereby the resident performs an act of disclosure. Furthermore, the attending staff may not be consistent in their expectations of what constitutes an adequate disclosure meeting. Objective structured clinical exams (OSCEs) can allow an opportunity to assess these skills. An OSCE station with a standardized patient (SP) allows an opportunity to evaluate these skills. The objective of this resource is to assess residents' communication skills involving the disclosure of a poor outcome to a SP using a patient encounter OSCE. Three OSCEs are presented here, with the intention that they be used as a pretest, a posttest after formal instruction in disclosure, and a delayed posttest to assess for long-term learning. In the first two stations, the disclosure OSCE is paired with, and preceded by, a counseling OSCE station. The residents are evaluated using guidelines for the disclosure of adverse events developed by the Canadian Patient Safety Institute and published by the Canadian Medical Protective Association. These OSCEs have been used successfully at our institution to assess disclosure, and are the subject of two scholarly papers (pending publication) on disclosure.